2010
DOI: 10.1007/s10802-009-9378-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Unmet Mental Health Needs in Children of Formerly Homeless Mothers Living in a Supportive Housing Community Sector of Care

Abstract: This study reports psychosocial characteristics of a sample of 111 children (K to 2nd grade) and their mothers who were living in urban supportive housings. The aim of this study was to document the various types and degree of risk endemic to this population. First, we describe the psychosocial characteristics of this homeless sample. Second, we compared this homeless sample with a grade-matched, high-risk, school-based sample of children (n = 146) who were identified as showing early symptoms of disruptive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…It is a promising finding that homeless men in the Skid Row area are more likely to receive mental health care when they are also receiving substance abuse treatment, as prior research suggests that those being treated for substance abuse behavior should be screened for mental health problems and vice versa (Kavanagh and Connolly 2009; Lee et al 2010). Recent utilization of a drop-in center in the Skid Row area was also associated with mental health care utilization; such an association suggests that usage of other services, even those which may seem unrelated to mental health care specifically, may serve as important enabling gateways through which homeless men come to utilize mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…It is a promising finding that homeless men in the Skid Row area are more likely to receive mental health care when they are also receiving substance abuse treatment, as prior research suggests that those being treated for substance abuse behavior should be screened for mental health problems and vice versa (Kavanagh and Connolly 2009; Lee et al 2010). Recent utilization of a drop-in center in the Skid Row area was also associated with mental health care utilization; such an association suggests that usage of other services, even those which may seem unrelated to mental health care specifically, may serve as important enabling gateways through which homeless men come to utilize mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of utilization patterns suggests frequent contact with multiple social systems, particularly health care and child welfare (Culhane et al 2011; Park et al 2012). Homeless children are frequently treated in emergency departments, primary healthcare settings, and social service agencies (Cumella et al 1998; Weinreb et al 1998), but specialized mental health care utilization lags—particularly in light of the prevalence of psychosocial disorders (Buckner and Bassuk, 1997; Lee et al 2010; Redlener et al 2005). …”
Section: Homelessness and Child Mental Healthmentioning
confidence: 99%
“…Lee et al (2010) reported on the psychosocial characteristics of a sample of children and their mothers who were living in urban supportive housing. This selective risk sample was compared to a demographically similar sample of children from a school-based prevention study where children were recruited based on teacher ratings of children's aggressive/disruptive behavior.…”
Section: Resultsmentioning
confidence: 99%